(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Climate change affects all sections of the population, but women, especially in developingcountries, have to bear the major brunt of its negative impacts. This is because of their gender-basedroles and socio-economic-cultural factors, which restrict their mobility, level of education and skilldevelopment. This gives them a secondary status, thus exacerbating gender-based inequalities. Globalestimates by WHO indicate that about one in three women worldwide experience some form of violencein their lifetime. In the wake of climatic stresses and extremes, women may face increased violence, be itphysical, psychological, sexual, verbal or economic.The paper has shown evidence that women face increased violence during and after climatic stresses.The most prominent form of violence experienced included domestic violence, verbal abuse and sexualharassment in shelter homes or during the collection of resources for the household. Since climaticchanges and extremes are likely to increase in future, it is important to incorporate the linkage betweenclimate change and violence against women to design suitable adaptation frameworks and policies. Thiswill help in achieving various national and international sustainable development goals of genderequality.